Association Between Heavy Lifting - Recreational and Occupational - and Pregnancy Outcomes - Mioduszewska, Joanna; Rot, Paweł; Poniewozik, Piotr; Dziuba, Natalia; Sim, Aleksandra; Pernal, Maja; Roguska, Zofia; Zuzak, Andrzej Paweł; Poniewozik, Paweł; Grabowski, Krzysztof (Quality in Sport, 2026)
Background: For years, pregnant women were told to avoid heavy lifting and high-intensity movement. However, current research shows the distinction between different types of physical load. While recreational lifting and strength training offer positive health benefits, repetitive heavy lifting in a workplace setting can lead to negative clinical outcomes. Aim: The aim of this review is to evaluate the association between heavy lifting - both occupational and recreational - and various pregnancy outcomes, including preterm birth, fetal growth, and maternal health, based on recent clinical literature. Methodology: A review of clinical guidelines and meta-analyses from 2016–2025 was conducted using PubMed and Google Scholar. Results: Findings indicate that occupational lifting (repetitive loads >10–15 kg) is associated with a modest increase in preterm birth and miscarriage risk, particularly when combined with prolonged standing. In contrast, recreational heavy resistance training (HRT) showed no significant correlation with adverse neonatal outcomes or pelvic floor dysfunction. Furthermore, structured exercise significantly reduces the incidence of gestational diabetes and hypertensive disorders. Conclusions: The impact of lifting is context dependent. Occupational strain requires ergonomic intervention, while structured, voluntary strength training is safe and protective for maternal health.